2019
DOI: 10.1093/bioinformatics/btz311
|View full text |Cite
|
Sign up to set email alerts
|

SPLATCHE3: simulation of serial genetic data under spatially explicit evolutionary scenarios including long-distance dispersal

Abstract: Summary SPLATCHE3 simulates genetic data under a variety of spatially explicit evolutionary scenarios, extending previous versions of the framework. The new capabilities include long-distance migration, spatially and temporally heterogeneous short-scale migrations, alternative hybridization models, simulation of serial samples of genetic data and a large variety of DNA mutation models. These implementations have been applied independently to various studies, but grouped together in the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 53 publications
0
55
0
Order By: Relevance
“…We simulated biological invasions with various levels of interbreeding between two closely related taxa by using the program SPLATCHE3 (Currat et al, 2019). SPLATCHE3 is a spatially explicit program that allows the simulation of neutral genetic diversity.…”
Section: Simulation Frameworkmentioning
confidence: 99%
“…We simulated biological invasions with various levels of interbreeding between two closely related taxa by using the program SPLATCHE3 (Currat et al, 2019). SPLATCHE3 is a spatially explicit program that allows the simulation of neutral genetic diversity.…”
Section: Simulation Frameworkmentioning
confidence: 99%
“…An alternative scenario would involve the recolonization of Brittany by shoals composed of a mixture of the two shad's species with unequal abundance similarly to the Ocean sampling where most of the individuals are from one species and one or a few individuals belong to the other species. Previous studies had also found sympatric occurrence of both species at sea (Taverny, 1991 Highly polymorphic (Jolly et al, 2012;Martin et al, 2015) or genomewide (Catchen et al, 2013) neutral markers and spatially explicit simulation-based approach (Currat, Arenas, Quilodran, Excoffier, & Ray, 2019) should be able to shed new light on the demographic aspect of hybridization during this recent northern shad recolonization event.…”
Section: Similar Observation Was Made Inmentioning
confidence: 94%
“…Spatially explicit computer simulations. We performed spatially explicit computer simulations with the evolutionary framework SPLATCHE3 34 . Information about the applied evolutionary models and landscape is presented in the Supplementary Material.…”
Section: Sample Collection and Ethical Statementsmentioning
confidence: 99%